Pendidikan Sains untuk Pemecahan Masalah dalam Islam - Muhammad Jamil. E (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2023)
Science education in Islam plays an important role in solving problems faced by mankind. By integrating science and faith values, science education aims to create individuals who are not only knowledgeable, but also have noble character. In Islam, science is considered a means to understand Allah's creation and use it for the good of mankind. Science education helps develop technologies and solutions that improve people's well-being, protect the environment and promote health. The ethics and morals embodied in Islamic teachings ensure that the application of science does not harm people or nature. In addition, science education also encourages the development of the character of honest and responsible scientists, as well as critical and creative attitudes. Thus, science education in Islam is not only about scientific understanding, but also about the application of science to achieve social justice, prosperity and the advancement of global civilization Abstrak Pendidikan sains dalam Islam memainkan peran penting dalam pemecahan masalah yang dihadapi umat manusia. Dengan mengintegrasikan ilmu pengetahuan dan nilai-nilai keimanan, pendidikan sains bertujuan untuk menciptakan individu yang tidak hanya berpengetahuan, tetapi juga berakhlak mulia. Dalam Islam, ilmu pengetahuan dianggap sebagai sarana untuk memahami ciptaan Allah dan menggunakannya untuk kebaikan umat manusia. Pendidikan sains membantu mengembangkan teknologi dan solusi yang meningkatkan kesejahteraan masyarakat, menjaga lingkungan, dan memajukan kesehatan. Etika dan moral yang terkandung dalam ajaran Islam memastikan bahwa penerapan ilmu pengetahuan tidak merugikan manusia atau alam. Selain itu, pendidikan sains juga mendorong pengembangan karakter ilmuwan yang jujur dan bertanggung jawab, serta sikap kritis dan kreatif. Dengan demikian, pendidikan sains dalam Islam bukan hanya tentang pemahaman ilmiah, tetapi juga tentang penerapan ilmu untuk mencapai keadilan sosial, kesejahteraan, dan kemajuan peradaban global